Bioactive Lipid Mediators in the Initiation and Resolution of Inflammation after Spinal Cord Injury. (1st July 2021) - David, Samuel; López-Vales, Rubén
Highlights: Inflammation contributes to secondary damage after spinal cord injury. Bioactive lipid mediators influence inflammation. In general omega-6 fatty acid derivatives initiate and promote inflammation. While omega-3 fatty acid derivatives resolve inflammation. Abstract: Neuroinflammation is a prominent feature of the response to CNS trauma. It is also an important hallmark of various neurodegenerative diseases in which inflammation contributes to the progression of pathology. Inflammation in the CNS can contribute to secondary damage and is therefore an excellent therapeutic target for a range of neurological conditions. Inflammation in the nervous system is complex and varies in its fine details in different conditions. It involves a wide variety of secreted factors such as chemokines and cytokines, cell adhesion molecules, and different cell types that include resident cell of the CNS, as well as immune cells recruited from the peripheral circulation. Added to this complexity is the fact that some aspects of inflammation are beneficial, while other aspects can induce secondary damage in the acute, subacute and chronic phases. Understanding these aspects of the inflammatory profile is essential for developing effective therapies. Bioactive lipids constitute a large group of molecules that modulate the initiation and the resolution of inflammation. Dysregulation of these bioactive lipid pathways can lead to excessive acute inflammation, and failure to resolve this by specialized pro-resolution lipid mediators can lead to the development of chronic inflammation. The focus of this review is to discuss the effects of bioactive lipids in spinal cord trauma and their potential for therapies.